STRATEGIC MANAGEMENT FOR CHARACTER EDUCATION STRENGTHENING IN NON-FORMAL EDUCATION: A CASE STUDY OF PKBM LABORA EDUKASI - Kesumayani, Heni (UIN Sunan Gunung Djati Bandung, 2025)
While character education has received increasing policy attention in Indonesia, limited research has examined how Pusat Kegiatan Belajar Masyarakat (PKBM), or Community Learning Centers—particularly those serving marginalized populations—strategically manage character development initiatives. This study investigates PKBM Labora Edukasi in Bogor, which employs a three-phase strategic model—planning, implementation, and evaluation—through contextual and collaborative approaches. Adopting a descriptive qualitative methodology, data were collected through in-depth interviews, participant observation, and document analysis to evaluate the implementation of the Character Education Strengthening Program (CESP). The program embeds character values into daily learning routines, utilizes tutors as role models, fosters partnerships with local Islamic boarding schools and private companies, and engages learners in context-based, experiential activities. The results indicate significant improvements in learner discipline, religiosity, civic engagement, and entrepreneurial mindset. These findings underscore the critical role of multi-stakeholder collaboration and contribute to the literature on strategic educational management by offering an adaptable framework for character education in resource-constrained, non-formal settings. The study highlights the potential for hybrid governance models to bridge national policy ambitions and grassroots realities, and it advocates for increased policy recognition and replication of such models in similar socio-educational contexts.